2007
DOI: 10.1016/j.ijpharm.2006.09.056
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of peptide transporters in MDCKII–MDR1 cell line as a model for oral absorption studies

Abstract: MDCKII-MDR1 cell line has been extensively selected as a model to study P-gp-mediated drug efflux. Recently, investigators have employed this cell line for studying influx of peptide prodrug derivatives of parent compounds which are P-gp substrates. Therefore, the objective of this study is to functionally characterize the peptide mediated uptake and transport of [ 3 H] Glycylsarcosine ([ 3 H] Gly-Sar), a model peptide substrate across MDCKII-MDR1 cells. [ 3 H] Gly-Sar uptake from apical (AP) and basolateral (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2
1

Relationship

5
3

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 20 publications
2
12
0
Order By: Relevance
“…The apical cell layer expresses functional efflux (P-gp or MRP2) as well as influx (peptide) transporters; which makes it convenient for us to compare the permeability values of both the parent drug and the prodrugs in the same cell line. This study was performed at pH 4 because highest permeabilities of Gly-Sar were found to be at this pH in the MDCKII-MDR1 cell line (Agarwal et al, 2007b). Permeabilities of VVL and GVL were found to be 6.37 and 2.58*10 −6 cm/sec respectively relative to 1.32*10 −6 cm/sec for LVR in MDCKII-MDR1 cells.…”
Section: Transport Across Mdckii-mdr1 and Mdckii-mrp2 Cellsmentioning
confidence: 98%
“…The apical cell layer expresses functional efflux (P-gp or MRP2) as well as influx (peptide) transporters; which makes it convenient for us to compare the permeability values of both the parent drug and the prodrugs in the same cell line. This study was performed at pH 4 because highest permeabilities of Gly-Sar were found to be at this pH in the MDCKII-MDR1 cell line (Agarwal et al, 2007b). Permeabilities of VVL and GVL were found to be 6.37 and 2.58*10 −6 cm/sec respectively relative to 1.32*10 −6 cm/sec for LVR in MDCKII-MDR1 cells.…”
Section: Transport Across Mdckii-mdr1 and Mdckii-mrp2 Cellsmentioning
confidence: 98%
“…Previously, we have reported that peptide transporters and efflux pumps (MDR1 and MRP2) are expressed on the apical surface of these cell lines (Agarwal et al, 2007a; Agarwal et al, 2007b). Moreover, we have also demonstrated that MDR1 and MRP2 efflux pumps play a significant role in diminishing A-B transport of LPV (Agarwal et al, 2008; Agarwal et al, 2007b; Patel et al, 2014b).…”
Section: Resultsmentioning
confidence: 97%
“…Samples were stored at −80 °C until further analysis with LCMS/MS. Transport studies across Caco2 cells were conducted at pH 5 and MDCK cells at pH 7.4 (Agarwal et al, 2008; Agarwal et al, 2007a). …”
Section: Methodsmentioning
confidence: 99%
“…For investigating substrate affinity towards peptide transporters, cellular uptake of [3H]-Gly-Sar was conducted in the presence and absence of prodrugs in MDCK-MDR1 cells. This cell line was selected as it highly expresses peptide transporters (44). Results obtained from this study are depicted in Fig.…”
Section: Cellular Uptake Studiesmentioning
confidence: 99%